Surgery for acromegaly: Indications and goals - Bray, David P.; Mannam, Sai; Rindler, Rima S.; Quillin, Joseph W.; Oyesiku, Nelson M. (Frontiers in Endocrinology, 2022)
Acromegaly is a disease that occurs secondary to high levels of GH, most often from a hormone-secreting pituitary adenoma, with multisystem adverse effects. Diagnosis includes serum GH and IGF-1 levels, and obtaining an MRI pituitary protocol to assess for a functional pituitary adenoma. Attempted gross total resection of the GH-secreting adenoma is the gold standard in treatment for patients with acromegaly for a goal of biochemical remission. Medical and radiation therapies are available when patients do not achieve biochemical cure after surgical therapy.